Mucinous adenocarcinoma of the rectum with breast and ocular metastases - Hisham, Raja B.; Thuaibah, Hashim; Alif Gul, Yunus Gul (Elsevier, 2006)
We present the case of a 32-year-old woman who, 10 months after abdominoperineal resection and total mesorectal excision for a locally advanced mucinous adenocarcinoma of the rectum, presented with local recurrence and metastases to the breast, spine, the left eye and orbit. Following surgery, due to the patient's personal reasons, adjuvant chemoradiation was not given. The patient died 2 months later, with disseminated cancer. To the best of our knowledge, breast as well as ocular metastasis in a patient with mucinous adenocarcinoma of the rectum has never been reported and, therefore, needs to be documented.